Determining factors and impact of household income on dairy cattle insurance in Nepal - Subedi, S.; Kattel, R. R. (Journal of Agriculture and Forestry University, 2022)
Nepalese agriculture insurance market is dominated by livestock sector and cattle are the most popular class of animal in livestock production system. This study was conducted to identify the determining factors and impact of household income on dairy cattle insurance. This study was based on the field survey conducted in Chitwan and Nawalparasi districts of Nepal. A total of 160 households were sampled using a stratified simple random sampling technique. Data were collected using a pre-tested interview schedule and focus group discussion (FGD) in 2017. The result of t-test showed annual household income, income from milk sell, and average cattle holding significantly higher in cattle insurer farmers than that of non-insurers. A probit model was used to assess the factors affecting the decision for the adoption of cattle insurance. The probit model revealed that cattle breed, access to loan, income from livestock, and number of cattle had a positive and significant relationship with the adoption of cattle insurance whereas, household size and district dummy had a negative and significant relationship with the adoption of cattle insurance. Income regression function revealed that the adoption of insurance, the number of cattle, and the district of the respondents had a positive and significant relation with income from livestock. The instrumental variable model adopted to combat endogeneity bias showed that adoption of insurance and district of the respondents had a positive and significant relation with income from livestock. Although the results are farmers specific, findings have implications for policymakers regarding promotion of improved breeds and facilitation of farm credit.